Sulfonylureas for Treatment of Periodontitis-Diabetes Comorbidity-Related Complications: Killing Two Birds With One Stone - Yang, Luxi; Ge, Qing; Ye, Zhitong; Wang, Lijing; Wang, Liping; Mashrah, Mubarak Ahmed; Pathak, Janak L. (Frontiers in Pharmacology, 2021)
Periodontitis is one of the most prevalent oral inflammatory diseases leading to teeth loss and oral health problems in adults. Periodontitis mainly affects periodontal tissue by affecting the host immune system and bone homeostasis. Moreover, periodontitis is associated with various systemic diseases. Diabetes is a metabolic disease with systemic effects. Both periodontitis and diabetes are common inflammatory diseases, and comorbidity of two diseases is linked to exacerbation of the pathophysiology of both diseases. Since bacterial dysbiosis is mainly responsible for periodontitis, antibiotics are widely used drugs to treat periodontitis in clinics. However, the outcomes of antibiotic treatments in periodontitis are not satisfactory. Therefore, the application of anti-inflammatory drugs in combination with antibiotics could be a treatment option for periodontitis-diabetes comorbidity. Anti-diabetic drugs usually have anti-inflammatory properties and have shown beneficial effects on periodontitis. Sulfonylureas, insulin secretagogues, are the earliest and most widely used oral hypoglycemic drugs used for type-2 diabetes. Studies have found that sulfonylurea drugs can play a certain role in the mitigation of periodontitis and inflammation. This article reviews the effects of sulfonylurea drugs on the mitigation of periodontitis-diabetes comorbidity-related inflammation, bone loss, and vascular growth as well as the involved molecular mechanisms. We discuss the possibility of a new application of sulfonylureas (old drug) to treat periodontitis-diabetes comorbidity.